PENGARUH LUMPUR LAUT TERHADAP PERTUMBUHAN DAN HASIL TANAMAN BAWANG MERAH PADA TANAH GAMBUT - yasma, ogei; Radian, Radian; Abdurrahman, Tatang (Jurnal Sains Mahasiswa Pertanian, 2019)
ABSTRACTThe purpose of this study was to determine the effects of coastal sediment on shallot growth and yield on peat soil and best dossage to optimal growth and yield.This research was conducted on January 10, 2018 until March 10, 2018 in research garden of Tanjungpura University Pontianak. The design used in this study was by using Completely Randomized Design (RAL) consist of seven treatments with four replicates, and each experimental unit consisted of 3 plant samples, the number of plant plants 84 units consist of l0 = 0 % coastal sediment, equivalent 0 kg of coastal sediment + 9 kg of peat; l1 = 2.5 % coastal sediment, equivalent 0.225 kg of coastal sediment + 9 kg of peat; l2 = 5 % of coastal sediment, equivalent to 0.45 kg of coastal sediment + 9 kg of peat; l3 = 7.5 % of coastal sediment, equivalent to 0.675 kg of coastal sediment + 9 kg of peat; l4 = 10 % coastal sediment, equivalent to 0.9 kg of coastal sediment + 9 kg of peat; l5 = 12.5 % coastal sediment, equivalent to 1.125 kg of coastal sediment + 9 kg of peat; and l6 = 15 % of coastal sediment, along with 1.35 kg of coastal sediment     + 9 kg of peat. Variables in this study were plant height, number of leaves, number of tubers per hill, fresh weight of tubers per hill, dry weight of tubers per hill and soil pH after incubation. Environmental observations are also made, such as observations of temperature and humidity. The results showed that coastal sediment has significant effect on top plant height, fresh weight of tubers per hill, and dry weight of tubers per hill. At dossage of 7,5 % - 15 % coastal sediment, effects can increase the growth and yield of shallot. Keywords : coastal sediment, production, shallot